(untitled) (International Seven Journal of Multidisciplinary, 2024)
This article explores instructional design and its role in the development of teaching and learning, with an emphasis on the integration of technology. The central focus is on how instructional design can create effective learning environments. The methodology includes a literature review on the use of digital tools, e-learning platforms and multimedia resources, which facilitate the creation and personalization of educational content. Authoring software and learning management applications allow the creation of interactive materials and the adaptation of teaching to the individual needs of students. However, the integration of technology into instructional design faces challenges, such as inequality of access, the need to create inclusive resources, and the continuous updating of content. Teacher training is critical to the effective use of new technologies, and overcoming resistance to change is an important aspect. The conclusion highlights that in order to maximize educational impact, it is essential to address these challenges and adhere to rigorous ethical considerations. An ongoing commitment to teacher education, the development of inclusive technologies, and the protection of student privacy are key to transforming education, making it more accessible, engaging, and effective.